1998
DOI: 10.1086/301762
|View full text |Cite
|
Sign up to set email alerts
|

A Missense Mutation in the Human Connexin50 Gene (GJA8) Underlies Autosomal Dominant “Zonular Pulverulent” Cataract, on Chromosome 1q

Abstract: CZP1, a locus for autosomal dominant "zonular pulverulent" cataract, previously had been linked with the Duffy blood-group-antigen locus on chromosome 1q. Here we report genetic refinement of the CZP1 locus and show that the underlying mutation is present in GJA8, the gene for connexin50. To map the CZP1 locus we performed linkage analysis using microsatellite markers on two distantly related branches of the original Ev. pedigree, which now spans eight generations. Significantly positive two-point LOD score (Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
182
2
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 303 publications
(191 citation statements)
references
References 40 publications
(45 reference statements)
2
182
2
2
Order By: Relevance
“…Changes in pH to a value of 6.8 would not have a major impact upon gap junctional intercellular communication between fiber cells, since wild-type human Cx50 channels remain open at that pH. Thus, our data suggest that changes in intracellular pH within the lens can have enormous effects for the survival of fiber cells and lens homeostasis and transparency, since alterations in gap junctional intercellular communication can lead to the formation of cataracts (White et al, 1998;Gong et al, 1997;Mathias, Rae & Baldo, 1997;Shiels et al, 1998;Pal et al, 1999). Moreover, because lens fiber cells also contain Cx46, consequences for lens survival would be influenced by the pH dependence of Cx46 channels and heteromeric Cx50-Cx46 channels.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Changes in pH to a value of 6.8 would not have a major impact upon gap junctional intercellular communication between fiber cells, since wild-type human Cx50 channels remain open at that pH. Thus, our data suggest that changes in intracellular pH within the lens can have enormous effects for the survival of fiber cells and lens homeostasis and transparency, since alterations in gap junctional intercellular communication can lead to the formation of cataracts (White et al, 1998;Gong et al, 1997;Mathias, Rae & Baldo, 1997;Shiels et al, 1998;Pal et al, 1999). Moreover, because lens fiber cells also contain Cx46, consequences for lens survival would be influenced by the pH dependence of Cx46 channels and heteromeric Cx50-Cx46 channels.…”
Section: Discussionmentioning
confidence: 77%
“…Moreover, because lens fiber cells also contain Cx46, consequences for lens survival would be influenced by the pH dependence of Cx46 channels and heteromeric Cx50-Cx46 channels. (A) Schematic drawing of the membrane topology of wild-type human Cx50 and two truncation mutants (top) and the aligned sequences of the regions of ovine and human Cx50 flanking the truncation sites (bottom) (based on Yang & Louis, 1996;Lin et al, 1997;Shiels et al, 1998 Transitions between different states of human Cx50 wild-type (A) and Cx50A294stop (B) gap junctional channels. A single gap junctional channel recorded from a cell pair expressing wildtype Cx50 at V j of +100 mV is shown in A and the circled region is shown below on an expanded time scale.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several human diseases have been linked to connexin polymorphisms (Bergoffen et al, 1993;Kelsell et al, 1997;Shiels et al, 1998) and directed mutations in mice have revealed diverse roles for connexins in transplacental nutrient transfer (Gabriel et al, 1998), ovulation (Simon et al, 1997), and cardiac development and function (Cx40, Cx43, and Cx45) (Kanter et al, 1994;Reaume et al, 1995;Ewart et al, 1997;Simon et al, 1998).…”
Section: Introductionmentioning
confidence: 99%